Assessing the risk of invasion of species in the pet trade in Brazil - da Rosa, Clarissa Alves; Zenni, Rafael; Ziller, Sílvia R.; de Almeida Curi, Nelson; Passamani, Marcelo (Perspectives in ecology and conservation, 2018)
•Six mammal pet species were assessed, all resulting in very high risk of invasion.•Rodents resulted the highest risk level among our analyses.•Reproductive traits account for the major part of the high risk of evaluated species.•Food group and ecological interactions were the main traits increasing risk scores of carnivores. Biological invasions are a major concern for biodiversity conservation. The release and escape of pet animals are the main sources of mammal invasions. Identifying potential invaders before they are introduced is a key tool for preventing the spread and impact of invasive alien species. Among the tools available for screening potential invaders are risk analysis protocols, which can also be used to assess the risk of species introduced in the past and limit or ban their import or commerce. We aimed to identify potential invasive mammals in the pet trade by applying a risk analysis protocol adapted to Brazil. Six alien mammals sold as pets in Brazil resulted high invasion risk. Rodents resulted the highest risk values. In order to prevent the release of invasive species through the pet trade it is necessary to avoid new introductions based on risk analysis, to identify species pathways, and to combat animal trafficking.